E-017 Impact of integrated cerebrovascular program on outcomes in patients with intracranial aneurysms. (4th July 2012) - Krishna, V; Turner, R; Chaudry, I; Turk, A
Abstract : Introduction: Recent evidence indicates that multidisciplinary care improves patient outcomes for cerebrovascular (CV) disease. A multidisciplinary, integrated CV program was recently instituted at a high volume tertiary referral center, providing the opportunity to evaluate patient outcomes before and after its introduction. Methodology: A retrospective chart review was performed on all new patient encounters for a 6-month time period each before and immediately after the introduction of the CV program, as well as at a more recent 6 month time period to evaluate long-term results. Data were collected on demographic variables, rupture status, medical comorbidities, hospital complications, in-hospital procedures, hospital course, and modified Rankin score at discharge and follow-up. Results: The total number of patients treated increased from 55 in the 6-month time period before the introduction of CV program to 112 in the most recent time period (p<0.05). Both the number of surgical clipping and endovascular coiling procedures increased (p<0.05). An increase in severity of illness was observed, with a significant increase in patients with multiple comorbidities (30.5% vs 34.7%, p=0.035). Mean length of hospital stay decreased from 12.22±13.26 days before the program to 9.23±12.04 days in the most current data, mainly due to a statistically significant decrease in intensive care unit length of stay between those time periods (p<0.05). Additionally, fewer systemic complications were observed in the most recent time period as compared to before the introduction of CV program. Conclusions: Creation of an integrated CV program at a large volume tertiary referral center resulted in better outcomes for an increased number of more medically complicated patients with intracranial aneurysms. This study provides preliminary data supporting the development of an integrated model of multidisciplinary care for the management of CV disease. Competing interests: None.